PROBLEMS OF THE SEISMICITY OF THE BAIKAL RIFT ZONE - Golenetsky S.I. (My University, 1990)
The results of investigations of the seismicity of the Baikal rift zone are considered on the basis of an instrumental survey of small shocks, macroseismic information on strong earthquakes of the past, and data on paleoseismic dislocations obtained from seismo-geological observations.The relations between the spatial pattern of the seismicity and various geological and geophysical parameters are analysed. Mean recurrence times of earthquakes and some peculiarities and trends of seismic processes are discussed. Unresolved problems of the seismicity of the zone are noted.